Progressive Control of Rashba State on Topological Dirac Semimetal KZnBi - Lee, Gyubin; Koo, Jahyun; Lee, Yeonghoon; Cha, Jaehun; Hyun, Jounghoon; Han, Kimoon; Lim, Chan Young; Denlinger, Jonathan D.; Kim, Sunghun; Kim, Sung Wng; Kim, Yeongkwan (Nano Letters, 2024)
Rashba states have been actively revisited as a platform for advanced applications such as spintronics and topological quantum computation. Yet, access to the Rashba state is restricted to the specific material sets, and the methodology to control the Rashba state is not established. Here, we report the Rashba states on the (001) surface of KZnBi, a 3D Dirac semimetal. Using angle-resolved photoemission spectroscopy and first-principles calculations, we investigated the evolution of Rashba states under different surface conditions controlled by alkali metal deposition. We observed that restoring surface ordering enables a Rashba state, which is absent in freshly cleaved surfaces. Interestingly, we were able to modify the dispersion of the Rashba state from an ordinary parabolic dispersion to a linearly dispersing Dirac-like state by additional alkali-metal deposition. Our findings provide a methodology for engineering the properties of Rashba states for advanced applications and redefine topological systems as generic hosts of Rashba states.
Keywords: 2DEG state; Advanced applications; Angle resolved photoemission spectroscopy; ARPES measurement; DFT calculation; First principle calculations; Metal deposition; Rashba state; Specific materials; Topological dirac semimetal; 2DEG states; ARPES measurements; DFT calculations; Rashba states; Topological Dirac semimetal